The Preparation of South Korean High School Students for International Communication - Walsh, Alexander (2013)
There has never been a greater need to develop South Korean students’ ability to use English as a means of international communication than now. While English has spread to all corners of the world (Graddol 1997) South Korea has seen an increased reliance on international trade and a significant increase in both foreign visitors to South Korea and South Koreans going abroad. Meanwhile, new models of English language teaching have evolved to account for the increased use of English involving one or more non-native speakers. One of the most prominent of these is English as a Lingua Franca (ELF), which promotes a shift from traditional English as a Foreign Language (EFL) models of teaching towards an approach that recognises and accounts for the important role non-native English speakers play (Seidlhofer 2004).